The role of alternative splicing coupled to nonsense-mediated mRNA decay in human disease - da Costa, Paulo (2021)
Alternative pre-mRNA splicing (AS) affects gene expression as it generates proteome diversity. Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that recognizes and selectively degrades mRNAs carrying premature translation-termination codons (PTCs), preventing the production of truncated proteins that could result in disease. Several studies have also implicated NMD in the regulation of steady-state levels of physiological mRNAs. In addition, it is known that several regulated AS events do not lead to generation of protein products, as they lead to transcripts that carry PTCs and thus, they are committed to NMD. Indeed, an estimated one-third of naturally occurring, alternatively spliced mRNAs is targeted for NMD, being AS coupled to NMD (AS-NMD) an efficient strategy to regulate gene expression. In this review, we will focus on how AS mechanism operates and how can be coupled to NMD to fine-tune gene expression levels. Furthermore, we will demonstrate the physiological significance of the interplay among AS and NMD in human disease, such as cancer and neurological disorders. The understanding of how AS-NMD orchestrates expression of vital genes is of utmost importance for the advance in diagnosis, prognosis and treatment of many human disorders.